Effects of isometric handgrip training in patients with cardiovascular disease: rationale and design of the ISOPRESS network - Breno Q. Farah; Lauro C. Vianna; Sergio Luiz C. Rodrigues; Marilia A. Correia; André L. Teixeira; Flávio M. D. de Andrade; Rodrigo P. Pedrosa; Sérgio R. Moreira; Mauro V. G. Barros; Nelson Wolosker; Gabriel G. Cucato; Raphael M. Ritti-Dias (Motriz: Revista de Educacao Fisica, 2018)
Abstract Meta-analytical studies have indicated that isometric handgrip training promotes significant reduction in blood pressure in hypertensive patients with similar or greater decreases in blood pressure than observed after aerobic and dynamic resistance training. However, several gaps in the literature still need to be addressed. Thus, we designed the ISOPRESS network group, which consists of a task force of different research groups aimed at analyzing the effects of isometric handgrip training on different contexts, parameters, and populations. Thus, the aim of this study was to describe the rationale and design behind the ISOPRESS, presenting the methods employed. The ISOPRESS questions involve whether isometric handgrip training is effective in hypertensives in different settings (ISOPRESS 1 - unsupervised training and ISOPRESS 2 - public health system), whether it works in patients with other cardiovascular diseases (ISOPRESS 3 - obstructive sleep apnea and ISOPRESS 4 - peripheral artery disease) and what are the mechanisms underlying the effects of isometric handgrip training in hypertensives (ISOPRESS 5 - neural mechanism). The study will yield information on the effectiveness of isometric handgrip training in different settings and patients with other cardiovascular diseases. Finally, it will help to understand the mechanisms involved in reducing blood pressure in hypertensives.